The role of government incentives in enhancing profitability of broiler farming in Peninsular Malaysia - Gabdo, Bashir Hamman; Ismail, Mohd Mansor; Masan, Ilmas Abdurofi; Abdul Wahab, Kamal Hisyam (Faculty of Veterinary Medicine, Universiti Putra Malaysia, 2015)
Data from 328 broiler farmers in Peninsular Malaysia are appraised for profit feasibility under government and non-government incentive scenarios. Net Present Value (NPV), Internal Rate of Return (IRR), Benefit-Cost Ratio (BCR) and Pay Back Period (PBP) financial indicators are analysed based 4 categories of government incentives; Pioneer Status (PS), Investment Tax Allowance (ITA), Accelerated Capital Allowance combined with Pioneer Status ACA (PS) and Accelerated Capital Allowance combined with Investment Tax Allowance ACA (ITA). On the whole, results reveal that provision of government incentives improves the profit feasibility of farmers and enhances better incomes. Analysis state basis indicates Perak, Johor and Kedah as the most feasible states, Kelantan and Penang are entirely not profitable and the rest are insignificantly profitable.